The influence of principal leadership and teacher performance on student learning - Sukarni Sukarni; Bukman Lian; Syaiful Eddy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The purpose of this study was to determine the significant effect of principal leadership and teacher performance on student learning outcomes in kindergarten, Lempuing Jaya district. The population in this study were 122 teachers with a sample of 93 teachers. The results of this study indicate that, (1). there is a significant influence of the Principal's Leadership on Teacher Performance with a value (tcount 5,552> ttable 1.99547) There is a significant effect of teacher performance on student learning outcomes with tcount 2180> ttable 1.99547) there is a significant influence of principal leadership and teacher performance on student learning outcomes with a value of fcount 15.553> ftable 3.29 and a significant level of 0.000 <0.05 then H0 is rejected and H1 is accepted. Vareabel Leadership can be concluded that the principal and teacher performance are simultaneously significant effect on Student Learning Outcomes in kindergarten Lempuing Jaya subdistrict Ogan Ogan Ilir.